Preparation method of biomass charcoal / magnesium composite material with low electron conductivity
By activate potassium hydroxide and self-exhaust pressure impregnation of biomass carbon, the electron conductivity is reduced, and a low-electronic conductivity of biomass carbon/magnesium composite material is prepared, which solves the problem of biomass carbon in the interface of magnesium ion batteries. The problem of failure improves the cycle stability and charge and discharge efficiency of magnesium batteries.
Patent Information
- Application Number
- CN202411292100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Biomass carbon, as an artificial protective interface for magnesium ions, is prone to failure during battery circulation, mainly due to its high electron conductivity, resulting in reduction and decomposition of the interface at the electrolyte and protective layer, and failure.
Chemical activation of biomass carbon by potassium hydroxide destroys its conjugated structure, reduces electron conductivity, and prepares low-electron conductivity biomass carbon/magnesium composite materials as magnesium ion conductivity using self-exhaust pressure impregnation technology. interface.
It significantly improves the reversible deposition/peel cycle and cycle stability of the magnesium metal negative electrode, improves the charge and discharge efficiency, extends the service life of the battery, and converts cheap natural biomass materials into high-performance magnesium ion battery negative electrode materials.
Smart Images

Figure CN119153698A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modification of a novel composite material and a preparation method thereof. Background Art
[0002] The development of high energy density and environmentally friendly rechargeable batteries has become the focus of many scientific researchers. With the increasing requirements for energy density and high safety in future applications and the current limited lithium resources, current lithium-ion batteries are not expected to be sufficient to meet the needs of this rapidly growing market. Magnesium metal is a promising candidate for super lithium-ion battery anodes because the capacity of the magnesium metal anode in rechargeable magnesium batteries (2230mAh g -1 ) is almost a commercial lithium battery (graphite, 372mAh g -l ) and a low reduction potential (-2.37 V vs standard hydrogen electrode). In addition, magnesium metal has the property of producing less dendrites under electrochemical conditions, in sharp contrast to lithium, and has high safety performance, high energy density, low price and environmental friendliness, which has attracted more and more attention.
[0003] In conventional electrolytes, the ion-passivating interfacial layer generated by the reduction of chemically unstable solvated species usually hinders the Mg 0 / Mg 2+ reaction. One solution is to reduce the Mg 2+ The interaction between Mg and solvent prevents 2+ However, the reversible deposition / stripping chemistry of magnesium required for operation can only be achieved with solid electrolytes that offer a wide voltage window but slow kinetics, or with highly corrosive and oxidatively unstable electrolytes such as Grignard reagents. Another solution is to construct a high Mg ion conducting interface that allows reversible Mg 2+ Deposition / stripping, which has recently been achieved through polymer coating, alloying, inorganic halogen compound modification and gas phase chemical adsorption. However, the electronic conductivity of this artificial magnesium ion conductive interface is a key parameter that limits its effectiveness. If the electronic conductivity of the interface layer is high, it is easy to undergo reduction and decomposition at the interface between the electrolyte and the artificial protective layer, thereby forming a new passivation layer that renders the artificial protective interface ineffective. A large number of studies have confirmed that biochar has the potential to serve as a magnesium ion conductive interface. However, since biochar itself has a certain electronic conductivity, biochar is prone to failure during battery cycling when used as an artificial magnesium ion protective interface. Therefore, a simple and low-cost method is urgently needed to further reduce the electronic conductivity of biochar, so that the modified biochar can serve as an artificial magnesium ion protective interface layer. Summary of the invention
[0004] In order to solve the problem that biochar has electronic conductivity and is easily ineffective as an artificial protective interface for magnesium ions during battery cycling, the present invention provides a method for preparing a biochar / magnesium composite material with low electronic conductivity.
[0005] The method for preparing the biomass carbon / magnesium composite material with low electronic conductivity of the present invention is carried out according to the following steps:
[0006] 1. Weighing materials: weigh lump biochar, potassium hydroxide and pure magnesium as raw materials;
[0007] 2. Preparation of biochar and potassium hydroxide mixture:
[0008] The biomass charcoal and potassium hydroxide powder solid weighed in step 1 are fully mixed and placed in a crucible to prepare for the preparation of activated biomass charcoal;
[0009] Alternatively, the potassium hydroxide weighed in step 1 is prepared into a potassium hydroxide aqueous solution, and then the biomass charcoal is immersed in the potassium hydroxide solution and stirred, and then the biomass charcoal is filtered and placed in a vacuum oven for drying to obtain a dry biomass charcoal and potassium hydroxide mixture, and the mixture is placed in a crucible;
[0010] 3. Preparation of activated biochar:
[0011] The mixture of biochar and potassium hydroxide obtained in step 2 is heated and kept warm under a protective atmosphere, the potassium hydroxide activates the biochar during the heat treatment process, and then cooled with the furnace under the protective atmosphere to room temperature to obtain activated biochar;
[0012] 4. Preparation of modified biomass carbon / magnesium composite materials:
[0013] The activated biochar obtained in step 3 was washed until the pH value was neutral, and then dried in a vacuum oven. Finally, a modified biochar / magnesium composite material was prepared by pressure infiltration under a protective atmosphere.
[0014] The present invention has the following beneficial effects:
[0015] 1. The present invention provides a method for preparing a biomass carbon / magnesium composite material with low electronic conductivity, wherein the biomass carbon is chemically activated by potassium hydroxide to destroy the conjugated structure of the material, and the electronic conductivity of the biomass carbon is effectively reduced, and the modified biomass carbon / magnesium composite material is synthesized by self-exhaust pressure infiltration technology. The modified biomass carbon as an artificial magnesium ion conductive interface significantly improves the number of reversible deposition / stripping cycles of the magnesium metal negative electrode in conventional electrolytes, and effectively improves the cycle stability and charge and discharge efficiency.
[0016] 2. As we all know, a large amount of waste wood and biomass waste is used for burning to generate electricity, discarded as garbage, or buried for agricultural planting. The present invention realizes the conversion of low-cost natural biomass materials into magnesium ion battery negative electrode materials with excellent performance. The present invention improves the electronic conductivity properties of natural biomass materials, making them more effectively play the properties of functional materials.
[0017] 3. The present invention has low cost, renewable raw materials and is environmentally friendly, and the process is simple. A significant improvement in performance can be achieved through a simple activation treatment, which meets the requirements of industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the XRD pattern of the modified biochar obtained in Example 1;
[0019] Figure 2 These are the experimental results of the electronic conductivity test of the modified biomass carbon / magnesium composite material and the unmodified biomass carbon / magnesium composite material obtained in Example 1. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0021] Specific implementation method 1: The preparation method of the biomass carbon / magnesium composite material with low electronic conductivity in this implementation method is carried out according to the following steps:
[0022] 1. Weighing materials: weigh lump biochar, potassium hydroxide and pure magnesium as raw materials;
[0023] 2. Preparation of biochar and potassium hydroxide mixture:
[0024] The biomass charcoal and potassium hydroxide powder solid weighed in step 1 are fully mixed and placed in a crucible to prepare for the preparation of activated biomass charcoal;
[0025] Alternatively, the potassium hydroxide weighed in step 1 is prepared into a potassium hydroxide aqueous solution, and then the biomass charcoal is immersed in the potassium hydroxide solution and stirred, and then the biomass charcoal is filtered and placed in a vacuum oven for drying to obtain a dry biomass charcoal and potassium hydroxide mixture, and the mixture is placed in a crucible;
[0026] 3. Preparation of activated biochar:
[0027] The mixture of biochar and potassium hydroxide obtained in step 2 is heated and kept warm under a protective atmosphere, the potassium hydroxide activates the biochar during the heat treatment process, and then cooled with the furnace under the protective atmosphere to room temperature to obtain activated biochar;
[0028] 4. Preparation of modified biomass carbon / magnesium composite materials:
[0029] The activated biochar obtained in step 3 was washed until the pH value was neutral, and then dried in a vacuum oven. Finally, a modified biochar / magnesium composite material was prepared by pressure infiltration under a protective atmosphere.
[0030] 1. This embodiment provides a method for preparing a biomass carbon / magnesium composite material with low electronic conductivity, wherein the biomass carbon is chemically activated by potassium hydroxide to destroy the conjugated structure of the material, and the electronic conductivity of the biomass carbon is effectively reduced, and the modified biomass carbon / magnesium composite material is synthesized by self-exhaust pressure infiltration technology. The modified biomass carbon as an artificial magnesium ion conductive interface significantly improves the number of reversible deposition / stripping cycles of the magnesium metal negative electrode in conventional electrolytes, and effectively improves the cycle stability and charge and discharge efficiency.
[0031] 2. As we all know, a large amount of waste wood and biomass waste is used for burning to generate electricity, discarded as garbage, or buried for agricultural planting. This embodiment realizes the conversion of low-cost natural biomass materials into magnesium ion battery negative electrode materials with excellent performance. This embodiment improves the electronic conductivity properties of natural biomass materials, so that they can more effectively exert the properties of functional materials.
[0032] 3. This implementation method has low cost, renewable raw materials and is environmentally friendly, and the process is simple. A significant improvement in performance can be achieved through a simple activation treatment, meeting the requirements of industrial production and application.
[0033] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mass ratio of the biochar and potassium hydroxide powder solid in step 2 is 1:1-20.
[0034] Specific implementation method three: This implementation method is different from specific implementation method one or two in that the concentration of the potassium hydroxide solution in step two is 1 to 20 mol / L.
[0035] Specific implementation mode 4: This implementation mode is different from any one of specific implementation modes 1 to 3 in that: the type of the crucible described in step 2 is a graphite crucible or a nickel crucible.
[0036] Specific implementation method five: This implementation method is different from specific implementation methods one to four in that: in step two, the biochar is placed in the potassium hydroxide solution and stirred at a speed of 100 to 600 rpm for 2 to 24 hours.
[0037] Specific embodiment 6: This embodiment is different from any one of specific embodiments 1 to 5 in that: the heat treatment heating rate of the biochar and potassium hydroxide mixture described in step 3 is 2 to 10°C / min.
[0038] Specific embodiment seven: This embodiment differs from any one of specific embodiments one to six in that: the heat treatment temperature of the biochar and potassium hydroxide mixture described in step three is 450-1000° C., and the protective atmosphere is helium, nitrogen or argon.
[0039] Specific embodiment eight: This embodiment differs from any one of specific embodiments one to seven in that: the heat treatment holding time of the biochar and potassium hydroxide mixture described in step three is 1 to 6 hours.
[0040] Specific embodiment nine: This embodiment differs from any one of specific embodiments one to eight in that: the method for washing the activated biochar in step four is: first soaking it in a hydrochloric acid solution with a concentration of 1 to 10 mol / L, and then washing it thoroughly with deionized water until the pH detection is neutral.
[0041] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that: the method for preparing modified biochar / magnesium composite materials by pressure infiltration as described in step four is: pure magnesium is prepared into a magnesium melt, and then the activated biochar is preheated, and after preheating, pressure infiltration is performed into the magnesium melt to completely fill the three-dimensional interconnected pores in the activated biochar; the preheating temperature is 600-650°C, and the pressure infiltration temperature is 800-890°C.
[0042] The following examples are used to verify the beneficial effects of the present invention:
[0043] Example 1: The preparation method of the biomass carbon / magnesium composite material with low electronic conductivity in this example is carried out according to the following steps:
[0044] 1. Weigh lump biochar, potassium hydroxide and pure magnesium as raw materials;
[0045] 2. Preparation of biochar and potassium hydroxide mixture:
[0046] The potassium hydroxide weighed in step 1 is prepared into a potassium hydroxide aqueous solution, and then the biomass charcoal is immersed in the potassium hydroxide solution and stirred, and then the biomass charcoal is filtered and placed in a vacuum oven for drying to obtain a dry biomass charcoal and potassium hydroxide mixture, and placed in a crucible;
[0047] The concentration of the potassium hydroxide solution is 4moL / L;
[0048] The crucible is a nickel crucible;
[0049] The biochar is placed in the potassium hydroxide solution and stirred at a speed of 400 rpm for 24 hours;
[0050] 3. Preparation of activated biochar:
[0051] The mixture of biochar and potassium hydroxide obtained in step 2 is heated and kept warm under a protective atmosphere, the potassium hydroxide activates the biochar during the heat treatment process, and then cooled with the furnace under the protective atmosphere to room temperature to obtain activated biochar;
[0052] The heating rate of the heat treatment of the biochar and potassium hydroxide mixture is 5°C / min, the holding temperature is 800°C, the protective atmosphere is nitrogen, and the holding time is 1h;
[0053] 4. Preparation of modified biomass carbon / magnesium composite materials:
[0054] The activated biochar obtained in step 3 was washed until the pH value was neutral, and then dried in a vacuum oven. Finally, a modified biochar / magnesium composite material was prepared by pressure infiltration under a protective atmosphere.
[0055] The activated biochar washing method is: first soaking it in a hydrochloric acid solution with a concentration of 2 mol / L, and then washing it thoroughly with deionized water until the pH test is neutral;
[0056] The method for preparing the modified biochar / magnesium composite material by pressure infiltration is: preparing pure magnesium into a magnesium melt, then preheating the activated biochar, and after preheating, performing pressure infiltration into the magnesium melt to completely fill the three-dimensional interconnected pores in the activated biochar; the preheating temperature is 640°C, and the pressure infiltration temperature is 880°C.
[0057] Comparative Example:
[0058] The preparation method of the unmodified biomass carbon / magnesium composite material is carried out according to the following steps:
[0059] 1. Weigh lump biochar and pure magnesium as raw materials;
[0060] 2. Preparation of biomass carbon / magnesium composite materials:
[0061] Unmodified biochar / magnesium composite materials were prepared by pressure infiltration under a protective atmosphere, wherein pure magnesium was prepared into a magnesium melt, and then the block biochar was preheated, and then pressure infiltrated into the magnesium melt to fill all three-dimensional interconnected pores in the block biochar; the preheating temperature was 640°C, and the pressure infiltration temperature was 880°C.
[0062] Figure 1 This is the XRD diagram of the modified biochar obtained in Example 1; as can be seen from Figure 1, the broad diffraction peak observed at a relatively low diffraction angle of 2θ=20-23o belongs to the 002 Bragg diffraction of the graphite domain, indicating that the activated hard carbon sample has small graphite domains, which is a typical feature of the hard carbon phase. Figure 2The electronic conductivity test results of the modified biomass carbon / magnesium composite material and the unmodified biomass carbon / magnesium composite material obtained in Example 1 are shown in Figure 1. After testing, the electronic resistance of the two systems was obtained by calculating the slope of the voltage-current curve. The electronic conductivity of the modified biomass carbon / magnesium composite material system was 3.25×10 -7 S cm -1 The electronic conductivity of the unmodified biomass carbon / magnesium composite material is 1.09×10 -4 S cm -1 The electronic conductivity of the system is reduced by three orders of magnitude, which effectively prevents the conventional electrolyte from being reduced at the artificial SEI interface and effectively limits the occurrence of side reactions between the electrolyte and the interface.
[0063] Example 2: The preparation method of the biomass carbon / magnesium composite material with low electronic conductivity in this example is carried out according to the following steps:
[0064] 1. Weighing materials: weigh lump biochar, potassium hydroxide and pure magnesium as raw materials;
[0065] 2. Preparation of biochar and potassium hydroxide mixture:
[0066] The biochar and potassium hydroxide powder solid weighed in step 1 are fully mixed and placed in a crucible to prepare for activation heat treatment of the biochar;
[0067] The mass ratio of the biochar to the potassium hydroxide powder solid is 1:3;
[0068] The crucible is a graphite crucible;
[0069] 3. Preparation of activated biochar:
[0070] The mixture of biochar and potassium hydroxide obtained in step 2 is heated and kept warm under a protective atmosphere, the potassium hydroxide activates the biochar during the heat treatment process, and then cooled with the furnace under the protective atmosphere to room temperature to obtain activated biochar;
[0071] The heating rate of the heat treatment of the biochar and potassium hydroxide mixture is 10°C / min, the insulation temperature is 450°C, the insulation time is 1.5h, and the protective atmosphere is argon;
[0072] 4. Preparation of modified biomass carbon / magnesium composite materials:
[0073] The activated biochar obtained in step 3 was washed until the pH value was neutral, and then dried in a vacuum oven. Finally, a modified biochar / magnesium composite material was prepared by pressure infiltration under a protective atmosphere.
[0074] The activated biochar washing method is: first soaking it in a hydrochloric acid solution with a concentration of 3 mol / L, and then washing it thoroughly with deionized water until the pH test is neutral;
[0075] The method for preparing the modified biochar / magnesium composite material by pressure infiltration is: preparing pure magnesium into a magnesium melt, then preheating the activated biochar, and after preheating, performing pressure infiltration into the magnesium melt to completely fill the three-dimensional interconnected pores in the activated biochar; the preheating temperature is 630° C., and the pressure infiltration temperature is 860° C.
[0076] After testing, the electronic resistance obtained by calculating the slope of the voltage-current curve of the two systems was found that the electronic conductivity of the modified biomass carbon / magnesium composite system was 2.06×10 -6 S cm -1 , which is reduced by at least two orders of magnitude compared to the unmodified biomass carbon / magnesium composite system (comparative example).
[0077] Example 3: The preparation method of the biomass carbon / magnesium composite material with low electronic conductivity in this example is carried out according to the following steps:
[0078] 1. Weighing materials: weigh lump biochar, potassium hydroxide and pure magnesium as raw materials;
[0079] 2. Preparation of biochar and potassium hydroxide mixture:
[0080] The biochar and potassium hydroxide powder solid weighed in step 1 are fully mixed and placed in a crucible to prepare for activation heat treatment of the biochar;
[0081] The mass ratio of the biochar to the potassium hydroxide powder solid is 1:4;
[0082] The crucible is a nickel crucible;
[0083] 3. Preparation of activated biochar:
[0084] The mixture of biochar and potassium hydroxide obtained in step 2 is heated and kept warm under a protective atmosphere, the potassium hydroxide activates the biochar during the heat treatment process, and then cooled with the furnace under the protective atmosphere to room temperature to obtain activated biochar;
[0085] The heating rate of the heat treatment of the biochar and potassium hydroxide mixture is 2°C / min, the insulation temperature is 600°C, the insulation time is 2h, and the protective atmosphere is nitrogen;
[0086] 4. Preparation of modified biomass carbon / magnesium composite materials:
[0087] The activated biochar obtained in step 3 was washed until the pH value was neutral, and then dried in a vacuum oven. Finally, a modified biochar / magnesium composite material was prepared by pressure infiltration under a protective atmosphere.
[0088] The activated biochar washing method is: first soaking it in a hydrochloric acid solution with a concentration of 6 mol / L, and then washing it thoroughly with deionized water until the pH test is neutral;
[0089] The method for preparing the modified biochar / magnesium composite material by pressure infiltration is: preparing pure magnesium into a magnesium melt, then preheating the activated biochar, and after preheating, performing pressure infiltration into the magnesium melt to completely fill the three-dimensional interconnected pores in the activated biochar; the preheating temperature is 620° C., and the pressure infiltration temperature is 870° C.
[0090] After testing, the electronic resistance obtained by calculating the slope of the voltage-current curve of the two systems was found that the electronic conductivity of the modified biomass carbon / magnesium composite system was 5.35×10 -6 S cm -1 , which is reduced by at least two orders of magnitude compared to the unmodified biomass carbon / magnesium composite system (comparative example).
Claims
1. A method for preparing a biomass carbon / magnesium composite material with low electronic conductivity, characterized in that: The preparation method of the biomass carbon / magnesium composite material with low electronic conductivity is carried out according to the following steps:
1. Weighing materials: weigh lump biochar, potassium hydroxide and pure magnesium as raw materials; 2. Preparation of biochar and potassium hydroxide mixture: The biomass charcoal and potassium hydroxide powder solid weighed in step 1 are fully mixed and placed in a crucible to prepare for the preparation of activated biomass charcoal; Alternatively, the potassium hydroxide weighed in step 1 is prepared into a potassium hydroxide aqueous solution, and then the biomass charcoal is immersed in the potassium hydroxide solution and stirred, and then the biomass charcoal is filtered and placed in a vacuum oven for drying to obtain a dry biomass charcoal and potassium hydroxide mixture, and the mixture is placed in a crucible; 3. Preparation of activated biochar: The mixture of biochar and potassium hydroxide obtained in step 2 is heated and kept warm under a protective atmosphere, the potassium hydroxide activates the biochar during the heat treatment process, and then cooled with the furnace under the protective atmosphere to room temperature to obtain activated biochar; 4. Preparation of modified biomass carbon / magnesium composite materials: The activated biochar obtained in step three is washed until the pH value is neutral, and then dried in a vacuum oven. Finally, the activated biochar and pure magnesium are pressure infiltrated under a protective atmosphere to obtain a modified biochar / magnesium composite material.
2. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The mass ratio of the biochar and potassium hydroxide powder solid described in step 2 is 1:1 to 20.
3. The method for preparing the low electron conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The concentration of the potassium hydroxide solution in step 2 is 1 to 20 mol / L.
4. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The type of the crucible in step 2 is a graphite crucible or a nickel crucible.
5. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: In step 2, the biochar is placed in the potassium hydroxide solution and stirred at a speed of 100 to 600 rpm for 2 to 24 hours.
6. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The heating rate of the heat treatment of the biochar and potassium hydroxide mixture in step 3 is 2 to 10°C / min.
7. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The heat treatment temperature of the biochar and potassium hydroxide mixture described in step 3 is 450-1000° C., and the protective atmosphere is helium, nitrogen or argon.
8. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The heat treatment time of the biochar and potassium hydroxide mixture described in step 3 is 1 to 6 hours.
9. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The method for washing the activated biochar in step 4 is: first soaking it in a hydrochloric acid solution with a concentration of 1 to 10 mol / L, and then washing it thoroughly with deionized water until the pH test is neutral.
10. The method for preparing the low electronic conductivity biomass carbon / magnesium composite material according to claim 1, characterized in that: The method for preparing the modified biochar / magnesium composite material by pressure infiltration described in step 4 is: preparing pure magnesium into a magnesium melt, then preheating the activated biochar, and after preheating, performing pressure infiltration into the magnesium melt to completely fill the three-dimensional interconnected pores in the activated biochar; the preheating temperature is 600-650°C, and the pressure infiltration temperature is 800-890°C.
Citation Information
Patent Citations
Supercapacitor electrode material and preparation method and application thereof
CN111196601A
Method for preparing cluster type aluminum-based composite material from graphene reinforced aluminum-based composite material waste
CN111945029A
Preparation method of biomass charcoal / magnesium composite material for negative electrode of magnesium battery
CN115513435A
Highly graphitized porous activated carbon material as well as preparation method and application thereof
CN116206907A
Sweeping gas process for production of activated carbon-based electrode materials
US20240140807A1
Cited By
Bio-based sodium ion electrode hard carbon negative electrode material and preparation method thereof
CN120039870A
